2020
DOI: 10.1186/s13071-020-3966-x
|View full text |Cite
|
Sign up to set email alerts
|

Yellow fever epizootics in non-human primates, Southeast and Northeast Brazil (2017 and 2018)

Abstract: Background: Yellow fever (YF) is a severe, infectious, but non-communicable arboviral hemorrhagic disease. In the last decades, yellow fever virus (YFV) infections have been prevalent in endemic areas in Brazil, affecting human and non-human primate (NHP) populations. Monitoring of NHP infection started in 1999, and reports of epizootic diseases are considered important indicators of viral transmission, particularly in relation to the sylvatic cycle. This study presents the monitoring of YFV by real-time RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 25 publications
(33 reference statements)
3
67
0
1
Order By: Relevance
“…However, we observed a strong negative correlation for detection of YFV in urban marmosets and higher median Cqs compared to Callicebus and Alouatta, suggesting lower genomic viral loads in those urban marmosets. Previous studies showed similar data when Callithrix presented higher Cqs (lower viral loads) than Alouatta during the recent YFV epizootics in Brazil [33]. On the other hand, we did not observe a difference among rural NHP (Callithrix, Alouatta, and Callicebus), which presented median estimates of genomic viral loads of 10E+6 times higher than Callithrix from urban and urban-rural transition areas.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 77%
See 1 more Smart Citation
“…However, we observed a strong negative correlation for detection of YFV in urban marmosets and higher median Cqs compared to Callicebus and Alouatta, suggesting lower genomic viral loads in those urban marmosets. Previous studies showed similar data when Callithrix presented higher Cqs (lower viral loads) than Alouatta during the recent YFV epizootics in Brazil [33]. On the other hand, we did not observe a difference among rural NHP (Callithrix, Alouatta, and Callicebus), which presented median estimates of genomic viral loads of 10E+6 times higher than Callithrix from urban and urban-rural transition areas.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 77%
“…However, the high infestation of Brazilian urban areas by Aedes aegypti poses a risk for YFV urban/ Aedes transmission [4,34,37,38]. Concerning Aedes, previous studies in Brazil have confirmed the competence of Aedes aegypti and Aedes albopictus, although the latter has shown low transmission competency to YFV [33].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…In São Paulo, marmosets are found in city centers close to humans, and sometimes are even used as pets. However, unlike Alouatta monkeys, which are highly susceptible to YFV 23,24 , marmosets may not be efficient YFV amplifier hosts due to low viral loads, as previously reported 25,26 . As our results demonstrate, Alouatta monkeys were restricted to forest areas, mainly in Atlantic Forest preserved areas, while most marmosets were found in squares and other green areas, in close proximity to humans.…”
Section: Discussionmentioning
confidence: 68%
“…This led to an exponential increase in transmission leading to over 2000 confirmed cases and over 600 deaths. Molecular analysis confirmed that the 2016-2017 epidemic strain was within the South American (SA) 1 genotype and that the epidemic resulted from direct sylvatic spill over to humans with the absence of sustained YFV transmission within the urban cycle [19,32,33]. Some studies have attributed the 2016 YF epidemic in YF non-endemic regions of Brazil to increased virulence of the new virus strain [31,32,34], others have blamed changing aspects of population and ecology, such as the rise in population density [34], the geographical expansion of the peri-urban mosquito Aedes albopictus [35], human encroachment into NHP habitats [36], and global warming [37].…”
Section: Introductionmentioning
confidence: 86%
“…Due to slow evolutionary rates and constant spillover, the phylogeny of YFV isolates from NHP are genetically similar to isolates from human outbreaks [12,17,18]. Consequently, in South America, regular surveillance of YFV outbreaks in NHP populations can be used as an epidemic preparedness strategy [12,19]. In addition to active surveillance, elimination of future YF outbreaks requires a comprehensive understanding of the current epidemiology and the influence of control and prevention methods, such as vaccination.…”
Section: Introductionmentioning
confidence: 99%